Religious Meaning-Making and Psychological Well-Being among Islamic Education Students in Sidoarjo: A Psychology of Religion Perspective - Sudirman; Moch. Zakki Mubarok; J. Nabiel Aha Putra; Nuril Hidayati Salsabilah (Lembaga Bale Literasi, 2026)
This study explores the process of religious meaning-making among Islamic Education students and its contribution to psychological well-being from the perspective of the psychology of religion. Psychological well-being has become a critical concern in higher education, as students face increasing academic pressures, social challenges, and future uncertainties. In this context, religious meaning-making functions as a psychological and spiritual mechanism that enables individuals to interpret life experiences within a meaningful religious framework. This study employs a qualitative approach using Interpretative Phenomenological Analysis (IPA). A total of 12–15 Islamic Education students were selected through purposive sampling. Data were collected through in-depth interviews, limited observations, and reflective documents, and analyzed using thematic analysis. The findings reveal three core processes: (1) reinterpretation of life experiences through a religious lens, (2) engagement in spiritual practices as coping strategies, and (3) integration of religious identity with life purpose. These processes contribute to the development of spiritual resilience, reflected in emotional stability, optimism, and a stronger sense of meaning in life. This study contributes to the psychology of religion by highlighting religious meaning-making as a key mechanism in enhancing psychological well-being and offers practical implications for spiritually oriented student development programs.